Differentiated analysis of charismatic leadership personality traits among grassroots managers in universities under the “Double First-Class” initiative - Liang, Qing-Qing; Liu, Lei; Yin, Fang (Frontiers in Psychology, 2025)
This study employs a dual methodology of literature review and questionnaire surveys using the Charismatic Leadership Questionnaire (C-K Scale) to explore the fundamental aspects of charismatic personality traits among 322 grassroots managers across various departments at Chang’an University. The research aims to identify the charismatic personality traits that university grassroots managers should exhibit in the context of the “Double First-Class” initiative. Key findings include: (1) The most significant charismatic leadership trait exhibited by grassroots leaders in universities is their focus on and understanding of their own needs. This is followed by their ability to articulate organizational strategic visions and their sensitivity to internal and external objective environments; (2) Female employees tend to perceive the leader’s charisma more in the dimensions of Strategic Vision Articulation (SVA) and Sensitivity to Member Needs (SMN) compared to male employees. Conversely, male employees are more likely to recognize the leader’s charisma in the Personal Risk (PR) dimension; (3) Male leaders are more inclined than female leaders to demonstrate the personality traits of Personal Risk (PR) and Unconventional Behavior (UB); (4) Leaders aged 30 and below exhibit the most significant behavioral traits in Strategic Vision Articulation (SVA), Self-Efficacy (SE), and Sensitivity to Member Needs (SMN); (5) With an increase in the scope of management, leaders demonstrate more prominent behavioral traits in the Strategic Vision Articulation (SVA) dimension. Leaders overseeing 8–15 people exhibit the most pronounced behavioral traits in the Sensitivity to Member Needs (SMN) dimension. This study contributes to a deeper understanding of the nuanced aspects of charismatic leadership among grassroots managers in academic institutions. It provides insights into how these traits align with the objectives of the “Double First-Class” initiative, offering valuable references for enhancing the leadership capabilities of grassroots managers in universities.